PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nuryanita Rusiah; Ronny Malavia Mardani; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe aim of this study is to find out and to examine capital structure, firm growth, firmsize and profitability toward service firm value which were registered in IndonesianStock Exchange (BEI) along with its independent variable i.e. capital structure, firmgrowth, firm size, and profitability dependent variable on firm value.This study used purposive sampling as research method that is sampling method bythe certain criteria. The amount of the sample in this study is 14 service industrycompanies which registered in Indonesian Stock Exchange. Research conducted inthe period 2014-2016 so that the data obtained as much as 42 samples. The analysisused is double regression analysis which preceded by classical assumptions testconsisting of normal test, heteroskesdasticity, multikolinearity, and autocorrelation.Hypothesis analysis is done by using F test and T test.The result of the study represent that 1) capital structure negatively affects the firmvalue 2) capital structure positively affects the firm value 3) firm size negativelyaffects the firm value and 4) profitability negatively affects the firm value.Keywords: Capital Structure, Firm Growth, Firm Size, Profitability, Firm Value.